2018
DOI: 10.1097/sap.0000000000001228
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Variations in Reimbursement for Breast Reconstruction

Abstract: We found that wide variations in reimbursement for breast reconstruction procedures exist and may preclude some surgeons from offering certain reconstructive options to a subset of patients. Understanding these discrepancies is a key first step in minimizing a potential care delivery disparity for this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…5 Hospital and system-level considerations, such as geographic access to academic centers offering reconstruction, type of hospital, and density of plastic surgeons, have also been found to contribute to differences in reconstruction rates. 22,24,25 Finally, provider-level considerations, including initial referral to a plastic surgeon and discussions about reconstruction from both surgical oncologists and plastic surgeons, have been found to vary by race, ethnicity, and insurance status, 7,20,26 and could contribute to our reported lower rates of reconstruction among minorities and the uninsured.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…5 Hospital and system-level considerations, such as geographic access to academic centers offering reconstruction, type of hospital, and density of plastic surgeons, have also been found to contribute to differences in reconstruction rates. 22,24,25 Finally, provider-level considerations, including initial referral to a plastic surgeon and discussions about reconstruction from both surgical oncologists and plastic surgeons, have been found to vary by race, ethnicity, and insurance status, 7,20,26 and could contribute to our reported lower rates of reconstruction among minorities and the uninsured.…”
Section: Discussionmentioning
confidence: 84%
“…Our study found that black and Hispanic women were significantly less likely to undergo reconstruction even after adjusting for known covariates, a trend that has been shown in studies using institutional data 10,17 ; earlier analyses of the Surveillance, Epidemiology, and End Results database 5,9,14,18 ; and both the National Surgical Quality Improvement Program and Nationwide Inpatient Sample. 6,19 Insurance status alone likely does not explain racial differences in reconstruction rates: although a higher proportion of minority patients have public insurance or lack insurance, limiting access to plastic surgeons and precluding some surgeons from offering reconstruction, 20 minorities remain significantly less likely to undergo reconstruction even after controlling for insurance type. 8,13,19,21,22 Other socioeconomic barriers likely also contribute to this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Though lymphedema surgery is typically reimbursed, Medicare has been linked to disparities in access to other covered reconstructive procedures such as breast reconstruction. 25,26 Arguments could be made that Medicare reimburses reconstructive procedures at lower rates than private insurers, which may preclude some hospitals from offering these procedures. However, in our cohort, all patients were offered surgery.…”
Section: Sociodemographic Factors May Impact Lymphedema-related Qualimentioning
confidence: 99%
“…The ability to reliably perform a DIEP flap is a marketable skill, not only in academic centers but also in private practice. As the breast reconstruction volume has increased due to increasing public awareness, insurance coverage, and mastectomy rates in the past decades, 20 breast reconstruction patients are abundant as patients for graduating microsurgeons. Graduates can market their microsurgical breast reconstructive skills in a variety of settings, perhaps even being the first to bring microsurgical breast reconstruction to a practice or community hospital.…”
Section: Discussionmentioning
confidence: 99%